Streptococcus agalactiae colonization is common among pregnant women with HIV infection and is neither predicted by hospital tier nor trimester in Mwanza, Tanzania - Paul H. Ngayomela; Richard Kiritta; Boniface A. Remi; Sophyrose T. Mboya; Nyambura Moremi; Dismas Matovelo; Fridolin Mujuni; Stephen E. Mshana; Claudia Daubenberger; Ruth N. Zadoks; Jeremiah Seni (BMC Pregnancy and Childbirth)
Abstract Background Streptococcus agalactiae, also known as Group B Streptococcus (GBS) is a member of the gastrointestinal tract and vaginal microbiota, and one of the commonest pathogens affecting pregnant women, neonates and infants. Its observed rate of colonization varies globally due to laboratory methods used, socio-cultural, epidemiological and clinical factors. This study therefore, aimed at determining the prevalence of GBS colonization and associated risk factors among HIV-infected and uninfected pregnant women in various health care facility tiers in Tanzania to guide priority screening and management. Methods A cross-sectional analytical study was conducted from February to June 2021 from the antenatal clinics in the primary, secondary and tertiary health care levels in the northwestern part of Tanzania involving 872 pregnant women. Demographic, obstetric and other clinical data were collected using a pre-tested structured questionnaire. Two swabs (vaginal and rectal) were collected and cultured-on blood agar and CHROMagarTMStrepB agar, followed by antimicrobial susceptibility testing. A two-sample test of proportions was used to compare the GBS prevalence in various sub-groups, and logistic regression analysis was deployed to ascertain the association between predictor variables and GBS colonization. Results The overall proportion of S. agalactiae colonization was 24.5% (214/872) [95% CI: 21.7 − 27.5%], and was significantly higher in the HIV infected group [63.1% (70/111)] than in the HIV-negative group [18.9% (144/761)]; OR (95% CI) = 7.33 (4.77–11.29, p-value < 0.001)]. Colonization was more prevalent in the rectal samples compared to vaginal samples [21.1% versus 8.83%, respectively; p-value < 0.001)] and S. agalactiae recovery was higher using CHROMagarTMStrepB agar compared to blood agar [24.4% versus 18.8%, respectively, p-value = 0.004]. There was no association between GBS colonization and health care facility levels or pregnancy trimesters. The S. agalactiae isolates were sensitive to ampicillin (100%), erythromycin (76.3%), clindamycin (84.4%) and vancomycin (98.1%). Conclusions Approximately a quarter of pregnant women are colonized by GBS in Mwanza, Tanzania; and colonization is remarkably higher among HIV-infected women. Ampicillin is recommended for prophylaxis and treatment of GBS. Introduction of routine GBS screening among all HIV-infected pregnant women using ultrasensitive CHROMagar™ Strep B agar is recommended, and molecular characterization of GBS isolates would be of interest to guide future vaccination strategies.